2019
DOI: 10.1038/s41598-019-42051-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved predictions of time-dependent drug-drug interactions by determination of cytosolic drug concentrations

Abstract: The clinical impact of drug-drug interactions based on time-dependent inhibition of cytochrome P450 (CYP) 3A4 has often been overpredicted, likely due to use of improper inhibitor concentration estimates at the enzyme. Here, we investigated if use of cytosolic unbound inhibitor concentrations could improve predictions of time-dependent drug-drug interactions. First, we assessed the inhibitory effects of ten time-dependent CYP3A inhibitors on midazolam 1′-hydroxylation in human liver microsomes. Then, using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…It should also be stressed that the concentration of a drug interacting with the enzyme may be different from the plasma concentration, which is usually readily available from clinical trials and later monitoring activities. It has been suggested that the use of unbound cytosolic concentrations—as a proxy for total/unbound plasma concentrations—would improve the prediction of in vivo DDIs (Filppula et al 2019 ). For practical reasons, we have listed the total plasma concentrations, not unbound concentrations, because there exists some uncertainty about which one is in better correlation with the drug concentration at the enzyme site.…”
Section: Cyp Substrates and Inhibitorsmentioning
confidence: 99%
“…It should also be stressed that the concentration of a drug interacting with the enzyme may be different from the plasma concentration, which is usually readily available from clinical trials and later monitoring activities. It has been suggested that the use of unbound cytosolic concentrations—as a proxy for total/unbound plasma concentrations—would improve the prediction of in vivo DDIs (Filppula et al 2019 ). For practical reasons, we have listed the total plasma concentrations, not unbound concentrations, because there exists some uncertainty about which one is in better correlation with the drug concentration at the enzyme site.…”
Section: Cyp Substrates and Inhibitorsmentioning
confidence: 99%
“…Conversely, some authors have shown comparable K I values whereas HHEP k inact was significantly reduced relative to HLM (Mao et al, 2013;Kimoto et al, 2019). More recently, it has been suggested that HLM inactivation parameters corrected for free cytosolic inhibitor concentrations estimated in HHEP could improve DDI predictions (Filppula et al, 2019). Mao and coworkers have evaluated HHEP as a system for measuring TDI, also adding plasma to the incubation medium to include the impact of protein binding on projection of in vivo DDI, with improved success (Mao et al, 2011;Mao et al, 2012;Mao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that F ic or Kp uu can explain differences in potency between isolated intracellular targets in biochemical high-throughput screening assays and the corresponding cellular assays (19). Drug response for intracellular targets in a variety of subcellular compartments including the cytosol, endosomes, and the nucleus has been successfully predicted, using our methodology for determination of F ic , F cyto , or F endo (19,32). Intracellular unbound drug concentrations are determined by combining the cellular accumulation ratio (Kp) with the fraction of unbound compound in the cell (f u,cell ).…”
Section: Discussionmentioning
confidence: 99%